Influence of constant magnetic field on the tribological parameters of rubbing couples steel-brass in surface active substances - Свирид, М.М. (Proceedings of National Aviation University, 2009)
Maintainability of surfaces of sensitive pairs of friction is analysed in surroundings with high electrical resistance in the conditions of friction. The model of tribological unit, determining conditions and conformities to the law of formation of protective tribological pellicles, is worked out. The parameters of reparation of friction surfaces are determined by a tribomagnetic method. The parameters of renewal of sensitive tribopairs are also defined on uncollapsible technologies by joint influence of triboelectrochemical method and tribomagnetic components.